2016
DOI: 10.1016/j.yfrne.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and neuroendocrine regulation of the postpartum brain

Abstract: Changes in expression of hundreds of genes occur during the production and function of the maternal brain that support a wide range of processes. In this review, we synthesize findings from four microarray studies of different maternal brain regions and identify a core group of 700 maternal genes that show significant expression changes across multiple regions. With those maternal genes, we provide new insights into reward-related pathways (maternal bonding), postpartum depression, social behaviors, mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 162 publications
0
40
0
1
Order By: Relevance
“…The brain is an organ that serves as the central nervous system among all vertebrate. Stroke is caused by occulusion of cerebral vessels or angiorhagia 1 - 4 . It is reported that stroke is the primary cause of disability and affects approximately 795,000 people annually.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is an organ that serves as the central nervous system among all vertebrate. Stroke is caused by occulusion of cerebral vessels or angiorhagia 1 - 4 . It is reported that stroke is the primary cause of disability and affects approximately 795,000 people annually.…”
Section: Introductionmentioning
confidence: 99%
“…In order to become maternal, the expression of hundreds of genes changes in the peripartum period . These changes are the bases for the numerous physiological, cellular and molecular adaptations the female has to go through in order to be prepared for the upcoming challenges as a mother.…”
Section: Introductionmentioning
confidence: 99%
“…4 In order to become maternal, the expression of hundreds of genes changes in the peripartum period. 5 These changes are the bases for the numerous physiological, cellular and molecular adaptations the female has to go through in order to be prepared for the upcoming challenges as a mother. Among these changes are increased signaling of the brain neuropeptide systems of oxytocin and vasopressin; while oxytocin has been known as a maternal neuropeptide since the 1980s, 6,7 vasopressin has been finally proven as such only in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…qPCR analysis was performed for five of the most highly-differentially expressed genes from [Moura et al, 2016;Gammie et al, 2016]. Whilst the direction of expression difference was generally consistent across the microarray and qPCR analyses for these genes, only two genes (Cyp2g1 and Stoml3)…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 95%